Komunikasi Bahasa Bali dalam Paruman Adat di Desa Bunutan Karangasem (Perspektif Sosiolinguistik) - I Wayan Jatiyasa (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This research is a qualitative research that aims to describe: (1) the form of communication in the Balinese language in the paruman adat in Bunutan Karangasem Village; (2) the obstacles faced when communicating Balinese in the paruman adat in Bunutan Karangasem Village; and (3) a strategy to overcome the obstacles of communicating Balinese language in the paruman adat in Bunutan Karangasem Village. Data collection methods use the look and interview method. The referral method is done with basic techniques and advanced techniques. The basic technique, namely tapping technology assisted with recording instruments, while the follow-up technique, which is using competent involvement-free listening techniques and note taking techniques are assisted with notebook instruments. The interview method uses a standardized interview. Based on the results and discussion, it can be concluded that: (1) the form of communication in the Balinese language in the paruman adat in the village of Bunutan Karangasem, namely using Balinese Madia language and pointing at the dialect of Bunutan Karangasem Village; (2) constraints when communicating Balinese language in paruman adat in Bunutan Karangasem Village are influenced, namely: directly (lack of knowledge about anggah-ungguhing basa Bali, no Balinese education, Indonesian/English language use is cooler, spontaneity due to forgetfulness, and habits) and indirectly (the impact of tourism, economic demands, and population heterogeneity); (3) a strategy undertaken to overcome the constraints of communicating Balinese language in the paruman adat in Bunutan Karangasem Village, namely: empowerment of Bali Provincial Bali Language Instructor; giving dharma discourse or counseling of Hinduism; free tutoring at the Indonesian Children's Foundation in Lean; and further study to college.